Creating a Screening Measure of Health Literacy for the Health Information National Trends Survey. Issue 4 (March 2016) - Champlin, Sara; Mackert, Michael
Purpose: Create a screening measure of health literacy for use with the Health Information National Trends Survey (HINTS). Design: Participants completed a paper-based survey. Items from the survey were used to construct a health literacy screening measure. Setting: A population-based survey conducted in geographic areas of high and low minority frequency and in Central Appalachia. Subjects: Two thousand nine hundred four English-speaking participants were included in this study: 66% white, 93% completed high school, mean age = 52.53 years (SD = 16.24). Measures: A health literacy screening measure was created using four items included in the HINTS survey. Scores could range from 0 (no questions affirmative/correct) to 4 (all questions answered affirmatively/correctly). Analysis: Multiple regression analysis was used to determine whether demographic variables known to predict health literacy were indeed associated with the constructed health literacy screening measure. Results: The weighted average health literacy score was 2.63 (SD = 1.00). Those who were nonwhite ( p = .0005), were older ( p < .0005), or had not completed high school ( p < .0001) tended to have lower health literacy screening measure scores. Conclusion: This study highlights the need to assess health literacy in national surveys, but also serves as evidence that screening measures can be created within existing datasets to give researchers the ability to consider the impact of health literacy.